Bio-based Products from Biomass - Zhaohui Tong; Letian Wang; Clay B. Olson (EDIS)
Biomass is renewable biological materials, such as trees, plants, grasses, vegetables, algae, food wastes, animal manures, and other organic wastes. Like fossil fuels, biomass can produce a wide selection of bio-based by-products while producing renewable energy. Learn more in this 5-page fact sheet written by Zhaohui Tong, Letian Wang, and Clay B. Olson, and published by the UF Department of Agricultural and Biological Engineering, September 2011. (AP photo/University of Florida/IFAS/Thomas Wright)